Shedding light into the relevance of telomeres in human reproduction and male factor infertility. Issue 2 (3rd October 2018) - Lopes, Ana Catarina; Oliveira, Pedro F; Sousa, Mário
Abstract: Sperm telomere length (STL) is a promising new parameter for sperm quality analysis that may elucidate the molecular mechanisms underlying the idiopathic cases of male factor infertility, which represent almost half of all the male factor infertility cases worldwide. Telomeres consist of nucleoprotein structures present at the ends of eukaryotic chromosomes, whose protective functions maintain the genomic stability. Their role in reproduction includes an active intervention during gametogenesis, fertilization, and preimplantation embryo development. In consonance, studies have shown that compromised telomere homeostasis is associated with male infertility. Since critically short telomeres have their function affected, assessing STL may be a fast and economic method for sperm quality analysis and expectantly contribute to improve the success of fertility treatments. This hypothesis is supported by several reports associating STL with seminal parameters, sperm genome integrity, and clinical outcomes. However, there are other studies in the literature that do not demonstrate these associations. Additionally, it is still not clear whether the lengthening mechanisms of telomeres occurring during early embryo development resume the inherited telomere length. Further research is essential to clarify the suitability of STL as a biomarker for male infertility, before it could be routinely implemented in medically assisted reproduction centers. Understanding the molecular mechanisms underlying STL function and dynamics will provide us new insights into the origins of male infertility and a possible new useful tool as an outcome predictor for assisted reproduction. Abstract : The importance of telomeres in human reproduction is increasingly evident and sperm telomere length has been suggested as a new biomarker for male infertility, possibly contributing to improve the success of fertility treatments.